The Logic of Conditional Belief. (20th April 2020) - Eva, Benjamin
Abstract: The logic of indicative conditionals remains the topic of deep and intractable philosophical disagreement. I show that two influential epistemic norms—the Lockean theory of belief and the Ramsey test for conditional belief—are jointly sufficient to ground a powerful new argument for a particular conception of the logic of indicative conditionals. Specifically, the argument demonstrates, contrary to the received historical narrative, that there is a real sense in which Stalnaker's semantics for the indicative did succeed in capturing the logic of the Ramseyan indicative conditional.